Regulation of C. elegans Neuronal Differentiation by the ZEB-Family Factor ZAG-1 and the NK-2 Homeodomain Factor CEH-28 - Ramakrishnan, Kalpana; Okkema, Peter G. (PLOS ONE, 2014)
The C. elegans pharyngeal neuron M4 is a multi-functional cell that acts as a cholinergic motor neuron to stimulate peristaltic pharyngeal muscle contraction and as a neuroendocrine cell secreting neuropeptides and growth factors to affect other cells both inside and outside the pharynx. The conserved transcription factors ZAG-1 and CEH-28 are co-expressed in M4 through most of development, and here we examine how these factors contribute to M4 differentiation. We find ZAG-1 functions upstream of CEH-28 in a branched pathway to activate expression of different sets of M4 differentiation markers. CEH-28 activates expression of the growth factor genes dbl-1 and egl-17, and the neuropeptide genes flp-5 and flp-2, while ZAG-1 activates expression of the serotonin receptor ser-7, as well as expression of ceh-28 and its downstream targets. Other markers of M4 differentiation are expressed normally in both zag-1 and ceh-28 mutants, including the neuropeptide gene flp-21 and the acetylcholine biosynthetic gene unc-17. Unlike ceh-28 mutants, zag-1 mutants completely lack peristaltic muscle contractions resulting from broader defects in M4 differentiation. Despite these defects, neither ZAG-1 nor CEH-28 are terminal selectors of the M4 phenotype, and we suggest they function in a hierarchy to regulate different aspects of M4 differentiation.